Hb Tianshui (HBB: C.119A > G) in Compound Heterozygosity with Hb S (HBB: C.20A > T) from Odisha, India. (3rd July 2016) - Meher, Satyabrata; Dehury, Snehadhini; Mohanty, Pradeep Kumar; Patel, Siris; Pattanayak, Chinmayee; Bhattacharya, Subhra; Das, Kishalaya; Sarkar, Biswanath
Abstract: We describe here a rare β-globin gene variant, Hb Tianshui [β39(C5)Glu→Arg; HBB : c.119A > G], detected during routine screening in Odisha, India. This is the second report of Hb Tianshui and the first to describe the cation exchange high performance liquid chromatography (HPLC) and DNA studies of two cases of this variant. Both cases had coinherited Hb S ( HBB : c.20A > T) but none presented with typical symptoms of sickle cell disease. One of the cases was heterozygous for a common α-thalassemia (α-thal) allele (−α 3.7 ) (rightward) (NG_000006.1: g.34164_37967del3804) and marginally raised Hb F percentage, while the other Hb S/Hb Tianshui case was completely benign and healthy. An atypical Asian Indian haplotype [+ − + − +] could be assigned to the Hb Tianshui variant. Hb Tianshui seems to mimic a few other Hb variants in cation exchange HPLC. However, we report two specific patterns in the chromatograms that are characteristic to Hb Tianshui. Combining an alkaline electrophoresis result with cation exchange HPLC at screening would be preferred to detect this rare variant, especially in regions with considerable frequency of Hb E [β26(B8)Glu→Lys; HBB : c.79G > A] or Hb S.